The Identification of EFL Students’ Vocabulary Mastery Problems in a Lexical Studies Class - Allvian Ika Fiki Susanto; Aziza Restu Febrianto (English Education Department - Universitas Nasional Karangturi, 2022)
The purpose of the research is to identify the vocabulary mastery problems faced by EFL students. The research method applied in this study is descriptive method. This study involves the first-semester students of English Education Department, Universitas Nasional Karangturi. The data of the research is collected by using test and questionnaire. The test result was used to identify the students’ vocabulary mastery problems. The questionare result was used to investigate the causes behind the students’ problems in vocabulry mastery. The result of the research shows three major problems of students’ vocabulary mastery faced in the lexical studies class. They are problems in mastering the use, meaning, pronunciation, and spelling of the English words. The causes of the problems are the multiple meanings of English words, differences of students’ first language (L1) spelling and pronunciation, and grammar system.